2019
DOI: 10.1038/s12276-019-0315-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of dichloroacetate against atherosclerosis via hepatic FGF21 induction mediated by acute AMPK activation

Abstract: Dyslipidemia-induced atherosclerosis, which has a risk of high morbidity and mortality, can be alleviated by metabolic activation associated with mitochondrial function. The effect of dichloroacetate (DCA), a general pyruvate dehydrogenase kinase (PDK) inhibitor, on in vivo energy expenditure in ApoE−/− mice fed a western diet (WD) has not yet been investigated. WD-fed ApoE−/− mice developed atherosclerotic plaques and hyperlipidemia along with obesity, which were significantly ameliorated by DCA administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…As in PDK knockout mice, DCA is effective in promoting glucose oxidation and lowering blood glucose in diabetes 75 , which is supported by recent evidence that DCA can exert a metformin‐like effect by promoting AMPK activation 14,73 . DCA also lowers cAMP accumulation, which was increased in db / db mice liver compared with db /+ mice 14 .…”
Section: Pdk Inhibitor As a Therapeutic Option In Metabolic Syndromementioning
confidence: 76%
See 2 more Smart Citations
“…As in PDK knockout mice, DCA is effective in promoting glucose oxidation and lowering blood glucose in diabetes 75 , which is supported by recent evidence that DCA can exert a metformin‐like effect by promoting AMPK activation 14,73 . DCA also lowers cAMP accumulation, which was increased in db / db mice liver compared with db /+ mice 14 .…”
Section: Pdk Inhibitor As a Therapeutic Option In Metabolic Syndromementioning
confidence: 76%
“…In Western diet‐fed apolipoprotein E ( ApoE ) −/− mice, DCA stimulates hepatic fibroblast growth factor 21 ( fgf21 ) messenger ribonucleic acid expression in an AMP‐activated protein kinase‐dependent manner. The increase was sufficient to increase serum FGF21 level and subsequent activity of BAT 73 (Figure 2c). Furthermore, an unbiased [U‐ 13 C]‐glucose tracer‐based metabolomics study showed that PDC flux activity is decreased, whereas Ser293 p‐PDC level is decreased on β3‐adrenergic activation in brown adipocyte 74 .…”
Section: Pdk Inhibitor As a Therapeutic Option In Metabolic Syndromementioning
confidence: 92%
See 1 more Smart Citation
“…Mice deficient for PDK4 in VSMCs exhibit a significant reduction in aortic calcium accumulation after vitamin D3 treatment compared with this accumulation in the control mice 22 . In ApoE −/− mice, inhibition of PDK4 by dichloroacetate (DCA), a wellestablished PDK inhibitor, attenuates atherosclerosis 23 . Recent studies from our laboratory and others have found that PDK4 activity is closely related to mitochondrial function in VSMCs 9,22 ; however, the exact mechanisms by which it affects pathological processes are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…BAs play a key functional role in the regulation of thermogenesis. The primary BAs (PBAs) such as cholic acid (CA) and secondary BAs (SBAs, metabolites derived from gut microbiota) such as deoxycholic acid (DCA) can increase the expression of UCP1 in WAT and BAT, and promote WAT browning and BAT thermogenesis [23,24]. In rodents, browning of WAT and adaptive thermogenesis of BAT are the major contributors to the enhancement of energy metabolism [25].…”
mentioning
confidence: 99%